Photovoltaic and Impedance Spectroscopic Investigation of MEH-PPV Blended CdS Quantum Dot Sensitized Solar Cell - Fatehmulla, Amanullah; Farooq, W. A.; Aslam, M.; Atif, M.; Ali, Syed Mansoor; Yahia, I. S.; Al-Dhafiri, A. M. (Amer Scientific Publishers, 2014)
Cadmium Sulphide (CdS) quantum dots (QDs) were deposited on nanostructured TiO2 film using Successive Ionic Layer Adsorption and Reaction (SILAR) method. The quantum dots were blended with a small quantity of MEH-PPV [Poly(2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinylene) conducting polymer powder mixed with polysulphide electrolyte. Nanostructured TiO2 on FTO glass and Platinum on FTO are used as photoelectrode and Counter electrode respectively. High resolution Transmission Electron Spectroscopy (HRTEM) image revealed that the CdS QDs adsorbed on TiO2. The optical properties of CdS QD with MEH-PPV on TiO2 film were studied by UV-Vis absorbance spectroscopy. The photovoltaic characteristics and impedance spectroscopic properties of CdS QDSSC were analyzed under air mass 1.5 illuminations. At the SILAR adsorption time of 5 min (10 cycles), the maximum conversion efficiency obtained for the FTO/TiO2/CdS QD +MEH-PPV/Pt/FTO configuration was 1.25% with highest short circuit current density and lowest charge transfer resistance. The measured characteristics of capacitance voltage showed a decreasing behavior from positive to negative capacitance due to injection of electrons from FTO electrode into TiO2.
Keywords: Nanostructure; Quantum Dot; MEH-PPV; Photovoltaic; Impedance Spectroscopy